Peripheral motor nerve conduction abnormality, muscle strength, and muscle wasting in patients with acute stroke: A pilot study. (May 2020) - Nozoe, Masafumi; Kubo, Hiroki; Kanai, Masashi; Yamamoto, Miho; Shimada, Shinichi; Mase, Kyoshi
Highlights: Lower-leg motor nerve conduction and muscle thickness were studied in acute stroke. The motor nerve conduction was not significantly different between limbs. The muscle thickness was significantly reduced in both limbs. Lower-leg muscle wasting was associated with motor nerve conduction in paretic. Abstract: Introduction: Stroke-related muscle wasting are important therapeutic targets to reduce disability in patients with stroke. Peripheral nerve conduction impairment is one reported factor that causes muscle wasting in these patients, but muscle strength, muscle wasting, and peripheral nerve conduction abnormality have not been examined in patients with acute stroke. We therefore investigated changes in lower-leg motor nerve conduction, muscle strength, and muscle wasting in patients with acute stroke. Methods: Patients with acute stroke were recruited. Their motor conduction velocity (MCV) and compound motor action potential (CMAP) amplitude in both sides of the common peroneal nerve, and lower paretic leg muscle strength by the Motricity Index (MI) and quadriceps muscle thickness (QMT) on both sides were measured at the time of admission and again 2 weeks later. Results: Eighteen patients with acute stroke (median [interquartile range], age = 68 [14] years; female = 4 [22%]) were enrolled. The MCV and CMAP amplitude were not significantly different between limbs. The QMT was significantly reduced in paretic (P = 0.014) and non-paretic (P = 0.003) limbs, but the lower paretic leg MI was increased (P = 0.0.001). There was a significant correlation between % differences in CMAP amplitude and % differences in QMT in the paretic limb (R = 0.604, P = 0.008), but not in the non-paretic limb (R = 0.225, P = 0.369). Conclusions: Lower-leg muscle wasting was associated with the change in CMAP amplitude in paretic limbs, but not in non-paretic limbs, in patients with acute stroke.